Does action follow intention with participation in home and group-based falls prevention exercise programs? An exploratory, prospective, observational study - Haines, T.; Hill, Keith; Vu, T.; Clemson, L.; Finch, C.; Day, L. (Elsevier Ireland Ltd, 2016)
© 2016 Elsevier Ireland Ltd. Background: Exercise for falls prevention is effective but of limited uptake in real life. The link between intention and behavior is central to many health-behavior models, but has not been examined in the falls prevention exercise context. Objective: This study examines this relationship and prospectively identifies factors associated with participation in group and home-based falls prevention exercise. Design: This was an observational study of community-dwelling adults in Australia >70 years of age with a 12 month follow-up (n = 394 commenced baseline assessment, n = 247 commenced follow-up). Methods: Intention, and other potential predictive factors examined, were measured at baseline while participation was measured using self-report at 12 month follow-up. Results: Between 65% and 72% of our sample at baseline agreed or strongly agreed they would participate in the falls prevention exercise programs. n = 27 respondents participated in home-based exercise during follow-up and had intention to do so while n = 29 who participated did not have intention. In contrast, n = 43 respondents participated in group exercise and had intention to do so compared to 11 who participated but did not intend to at baseline. Perception of personal effectiveness and previous exposure to the exercise intervention were most strongly predictive of future participation. Conclusion: More people who do not want to participate in home exercise actually participate in home exercise than people who do not want to participate in group exercise that actually do. It may be easier to convince people who do not want to participate in falls prevention exercise to participate in a home program.